MUTU DALAM PERSPEKTIF FEGEINBAUM DAN IMPLEMENTASINYA DALAM LEMBAGA PENDIDIKAN - Muhammad Fahrizal Amin (MANAGERE : Indonesian Journal of Educational Management, 2020)
Total Quality Management (TQM) is the thought of Arman V. Feigenbaum which was originally used to improve the quality of high quality in achievement of business world and production company’s. This thinking then adopted and applied to the world system of education units to achieve the same thing, namely high quality improvements that emphasize customer satisfaction. Customers of this education world, in addition to students, are also involved parents guardians of students, as well as the government as the supervisor of education and curriculum makers. This research uses library based. This study carries quality in the perspective of Feigenbaum and its implementation in educational institutions with TQM and considers the five pillars of TQM implementation in the world of education. That is; customer focus, total involment, measurement, commitment, and continuous and continuous improvement. While barriers to implementation in the world of education that implement TQM can be found according to the thoughts of Sharples et al namely; commitment, education and training, application and practice, standardization and recognition.